Double tail anomaly and surgical intervention - Khurram Ashfaq; Amjad Islam Aqib; Babar Rashid; Muhammad Asif; Muhammad Fakhar-; Rana Faisal Naeem; Zeeshan Ahmad Bhutta; Muhammad Shoaib; Asma Hamid (International Journal of Veterinary Science and Research - Peertechz Publications, 2019)
Congenital problems can be caused by genetic or chromosomal abnormalities. Some of these problems can be treated through different methods. These methods of treatment depend on the level defection. A twenty-fi ve days old female cross bred buffalo calf was presented at out-door of Department of Clinical Medicine and Surgery, Faculty of Veterinary Sciences, University of Agriculture Faisalabad with a complaint of an extra tail and maggots' infestation. On complete physical examination abnormal growth was suspected as congenital problem with the presence of second tail. Surgical intervention was proposed as line of action against this anomaly.